"Ion sliding" on graphene: a novel concept to boost supercapacitor performance. Issue 5 (24th April 2019) - Bellani, Sebastiano; Martín-García, Beatriz; Oropesa-Nuñez, Reinier; Romano, Valentino; Najafi, Leyla; Demirci, Cansunur; Prato, Mirko; Del Rio Castillo, Antonio Esau; Marasco, Luigi; Mantero, Elisa; D'Angelo, Giovanna; Bonaccorso, Francesco
Abstract : We demonstrate how single-/few-layer graphene flakes act as friction-free "ion slides" for supercapacitor electrolytes, boosting the electrochemical performance of commercial-like supercapacitors. Abstract : Efficient ionic transport in nanoporous carbon electrodes is pivotal for the development of high-rate electrochemical capacitive energy storage in supercapacitors (SCs). Over the past decade, the understanding of the charging/discharging mechanisms in nanostructured carbon electrodes and the elucidation of confinement and desolvation of ions in electrically charged carbon nanopores have spurred the development of advanced SCs holding ever-increasing energy density. Crucially, these advancements have to be accomplished without sacrificing the extraordinary power handling and cycling lifetime of the SC. In this work, we investigated the interaction between single-/few-layer graphene (SLG/FLG) flakes or activated carbon (AC) films and 1 M tetraethylammonium tetrafluoroborate (TEABF4 ) in propylene carbonate (PC) by lateral force microscopy (LFM) measurements. We unravel that the electrolyte nanotribology on SLG/FLG flakes incorporated into AC-based electrodes is effective at boosting the power performance of commercial-like SCs (active material mass loading ∼10 mg cm −2 ), thus maximizing the advantage of using nanoporous nanocarbon electrodes with high energy density. At a charge/discharge (CD) current density of 0.1 A g −1, our hybrid AC:SLG/FLG-based SC shows a 30% increase of specific capacitance ( C g ) compared to the reference device, i.e., the AC-based one ( C g from 76.8 F g −1 to 98.2 F g −1 ). At higher CD current densities (>1 A g −1 ), the AC-based device displays a resistive behaviour, while the AC:SLG/FLG-based SCs still exhibit a C g of 23.9 and 5.2 F g −1 at CD current densities as high as 2.5 and 5 A g −1, respectively. Beyond the control of the nanoporosity of carbon materials and the inter-ionic interaction of the electrolytes, the rationalization of the relationship between the nanotribology of nanocarbons and the performance of the corresponding SCs offers new opportunities to optimize the SC design compatibly with established high-throughput industrial manufacturing.